Impact of traumatic brain injury on sleep: an overview - Aoun R (Dove Medical Press, 2019)
Raissa Aoun,1 Himanshu Rawal,2 Hrayr Attarian,3 Ashima Sahni41Department of Neurology, Lebanese American University Medical Center – Rizk Hospital, Beirut, Lebanon; 2Department of Medicine, Medstar Union Memorial Hospital, Baltimore, MD, USA; 3Department of Neurology, Northwestern Memorial Hospital, Chicago, IL, USA; 4Division of Pulmonary, Critical Care, Sleep and Allergy, Department of Medicine, University of Illinois at Chicago, IL, Chicago, USACorrespondence: Ashima SahniDivision of Pulmonary, Critical Care, Sleep and Allergy, Department of Medicine, University of Illinois at Chicago (MC 719), Chicago, IL 60612, USATel +312 355 4806Email asahni@uic.eduAbstract: Traumatic brain injury (TBI) is a global health problem that affects millions of civilians, athletes, and military personnel yearly. Sleeping disorders are one of the underrecognized sequalae even though they affect 46% of individuals with TBI. After a mild TBI, 29% of patients have insomnia, 25% have sleep apnea, 28% have hypersomnia, and 4% have narcolepsy. The type of sleep disturbance may also vary according to the number of TBIs sustained. Diffuse axonal injury within the sleep regulation system, disruption of hormones involved in sleep, and insults to the hypothalamus, brain stem, and reticular activating system are some of the proposed theories for the pathophysiology of sleep disorders after TBI. Genetic and anatomical factors also come to play in the development and severity of these sleeping disorders. Untreated sleep disturbances following TBI can lead to serious consequences with respect to an individual’s cognitive functioning. Initial management focuses on conservative measures with progression to more aggressive options if necessary. Future research should attempt to establish the effectiveness of the treatments currently used, as well as identify manageable co-existing factors that could be exacerbating sleep disorders.Keywords: traumatic brain injury, neurobiology, sleep disorders, TBI, sleep